Causes and Results of Repeated Operations in Iatrogenic Lesions of the Biliary System (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Iatrogenic injuries, resulting from medical interventions, often necessitate repeat surgeries, whichpose significant challenges for patients and health-care systems. This retrospective study aimed to evaluate theoccurrence and outcomes of various procedures for iatrogenic injuries, focusing on liver and bile duct traumas.Methods: The study included 110 patients aged 34–72 years who underwent reoperation due to surgicalcomplications at two leading medical centers in Bishkek, Kyrgyzstan, from 2015 to 2023. Of these, 21 (19.3%)patients required additional surgery, primarily due to iatrogenic harm to the liver and bile ducts during initialoperations, predominantly laparoscopic cholecystectomies for cholelithiasis. The diagnostic approach incorporatedclinical assessment, imaging studies, and laboratory analysis. Results: Reoperations varied according to injurytype and severity, with immediate operations conducted on 17 (81%) patients and delayed reconstructive surgeriesperformed on 4 (19%) patients. Post-reoperation complications occurred in 5 (23.8%) patients, and the averagehospital stay was 14 days. The study reported a 4.8% mortality rate, highlighting the significant risks associatedwith surgical management of iatrogenic injuries. Conclusion: Effective management of these injuries requires acomprehensive approach that prioritizes patient safety, quality of care, and efficient resource utilization. Ongoingprofessional development, adherence to guidelines, and continued research on prevention and innovative surgicaltechniques are essential to reduce the occurrence of iatrogenic injuries and improve patient outcomes.